Multiple deadlocks in the development of nonprofit drugs - Cvek, Boris (Drug discovery today, 2022)
The current Coronavirus 2019 (COVID-19) pandemic has shown us that the pharmaceutical research community can organize and administer large nonprofit clinical trials (RECOVERY and SOLIDARITY) and achieve the swift development of common, unpatentable drugs for a new indication: in this case an old, inexpensive drug, dexamethasone, for COVID-19. Why is it that such nonprofit efforts are so rare and are not organized as a systemic, routine part of drug development in the public interest? Based on my own experience with repurposing the alcohol-abuse drug disulfiram (Antabuse) for cancer, I identify at least four serious deadlocks to development of nonprofit drugs. All of these obstacles should be addressed to leverage the potential of the COVID-19 pandemic for better future healthcare systems in all countries around the world.
Keywords: Nonprofit drugs; disulfiram; Organizations, Nonprofit; pandemie; poskytování zdravotní péče; Delivery of Health Care; Disulfiram; lidé; Biomedicine; Clinical trials; Dexamethasone; neziskové organizace; Pandemics; COVID-19; Humans